2022
DOI: 10.3389/fmicb.2022.869441
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of Host MicroRNAs in Flaviviruses Infection

Abstract: MicroRNAs (miRNAs) are small non-coding RNA that affect mRNA abundance or translation efficiency by binding to the 3′UTR of the mRNA of the target gene, thereby participating in multiple biological processes, including viral infection. Flavivirus genus consists of small, positive-stranded, single-stranded RNA viruses transmitted by arthropods, especially mosquitoes and ticks. The genus contains several globally significant human/animal pathogens, such as Dengue virus, Japanese encephalitis virus, West Nile vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…miR-92a is also less abundant in biting Pipiens relative to non-biting Molestus ( Table 1 ). In addition to suppressing the translation of endogenous mRNA transcripts, miRNAs can directly bind to viral genomes and inhibit viral replication [ 65 ]. Furthermore, Yen et al [ 47 ] used computational analyses to predict that miR-92a in A. aegypti binds to the positive-sense genomic viral RNA encoding the non-structural protein 5 (NS-5) of dengue virus I.…”
Section: Discussionmentioning
confidence: 99%
“…miR-92a is also less abundant in biting Pipiens relative to non-biting Molestus ( Table 1 ). In addition to suppressing the translation of endogenous mRNA transcripts, miRNAs can directly bind to viral genomes and inhibit viral replication [ 65 ]. Furthermore, Yen et al [ 47 ] used computational analyses to predict that miR-92a in A. aegypti binds to the positive-sense genomic viral RNA encoding the non-structural protein 5 (NS-5) of dengue virus I.…”
Section: Discussionmentioning
confidence: 99%
“…Host- and vector-derived ncRNAs also exert regulatory control over viral infections [ 106 ]. Certain miRNAs modulate viral replication by directly targeting viral genomic RNAs.…”
Section: Noncoding Rnas Regulate the Replication Of Flavivirusmentioning
confidence: 99%
“…As a type of small noncoding RNA, miRNAs can affect the expression of target genes involved in many BPs through target gene 3' UTR binding. After the viral invasion, the expression of host miRNAs changes, leading to immune escape and creating an environment that is conducive to virus survival (77). In this study, we identified 12 miRNAs that simultaneously targeted more than two hub genes and lncRNAs that targeted the corresponding miRNAs.…”
Section: )mentioning
confidence: 99%